2015
DOI: 10.1364/josab.32.002411
|View full text |Cite
|
Sign up to set email alerts
|

Theory of second-harmonic generation in a chirped 2D nonlinear optical superlattice under nonlinear Raman-Nath diffraction

Abstract: We analyze second harmonic generation (SHG) in a two dimensional nonlinear optical superlattice (NLOS) with its modulation period being chirped in the propagation direction and constant in the transverse direction. This results in efficient multiple SHG via nonlinear Raman-Nath diffraction. We obtain exact analytical expressions for a SH amplitude generated in chirped 2D NLOSs and for its quasi-phasematching bandwidth. The results of analytical calculations are in excellent agreement with the numerical ones. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It has been shown that the fundamental pulse duration can be readily characterized with single pulses by means of measuring the second harmonic beam profile by a spatial detector. The approach proposed can be used to calculate parametric interactions in oneand two-dimensional nonlinear photonic crystals [19,20]. …”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the fundamental pulse duration can be readily characterized with single pulses by means of measuring the second harmonic beam profile by a spatial detector. The approach proposed can be used to calculate parametric interactions in oneand two-dimensional nonlinear photonic crystals [19,20]. …”
Section: Resultsmentioning
confidence: 99%
“…They have been found to be promising for multiwavelength generation [8], the implementation of broadband parametric interactions [9], producing path-entangled photons [10] and multiple copies of beams carrying orbital angular momentum [11], and the observation of the nonlinear Talbot effect [12,13]. Up to now, 2D nonlinear photonic lattices with periodic [14], randomized [15], superimposed [16], and chirped [17] modulation of the nonlinear susceptibility sign in the propagation direction have been investigated. Among them, only periodic structures provide a specific reciprocal lattice vector for all the NRND orders, while the phase mismatches for different orders are different.…”
Section: Introductionmentioning
confidence: 99%
“…One of these is to use the dispersion property of QPM materials to obtain broadband QPM SHG with groupvelocity matching [1][2][3][4] (GVM) between the fundamental harmonic (FH) and second harmonic (SH) waves in periodically poled nonlinear crystals. Another method is to compensate the phase mismatch between interactive light waves through chirped nonlinear crystals, such as chirped periodically poled crystals [5,6], apodized chirped crystals [7], Bessel-chirped crystals [8] and chirped 2D nonlinear crystals [9]. Although these methods can broaden the acceptance bandwidth effectively, the acceptance bandwidth is still restricted in certain ranges.…”
Section: Introductionmentioning
confidence: 99%